Fresh-Cut Mango Best Management Practices Manual: HS1443/HS1443, 5/2023 - Brecht, Jeffrey K.; Plotto, Anne; Marín-Gozalbo, Anna; Goodrich, Renee (EDIS, 2023)
The National Mango Board (NMB), an instrumentality of the US Department of Agriculture, commissioned this work to assist the mango industry. Every effort has been made to ensure the accuracy and completeness of the information. However, NMB makes no warranties, expressed or implied, regarding errors or omissions and assumes no legal liability or responsibility for loss or damage resulting from the use of information contained in this document. Mention of a trademark or proprietary product is for identification only and does not imply a guarantee or warranty of the product by the US Department of Agriculture. The US Department of Agriculture prohibits discrimination in all its programs and activities on the basis of race, color, national origin, gender, religion, age, disability, political beliefs, sexual orientation, and marital or family status.